Reformed polyimide/nanocrytalline cellulose for gas separation - Norazlianie, Sazali; Wan Norharyati, Wan Salleh; Ahmad Fauzi, Ismail; Mimi Sakinah, Abdul Munaim (2021)
Manufactured via single step coating-carbonization cycle to reduce production time and cost. Excellent thermal resistance and chemical stability. Perfect product for wide range of gas separation applications. Present various carbonization condition for supported carbon membrane.